The translucency of human teeth and its relation to esthetic restorative materials - Basudan, Thuraya Abdulrahim; Alqahtani, Saif Juraythi; Alsalmh, Omar Abdulaziz; Kensara, Ekhlas Ishaq; Mughafi, Mohammed Fareed Al; Alamri, Naif Abdullah; Hakami, Mohammed Bishi; Moussa, Wiaam Ibrahim; Alshehri, Mohammed Abdulaziz; Fayi, Mohammed Ali; Mayyan, Abdullah Mohmmed (International Journal Of Community Medicine And Public Health, 2021)
The main factor that can determine the harmonization and depth of color restorations for the adjacent other restorations or other teeth is the translucency of these restorations. Many factors can affect the translucency and color of the restoration material, including translucency parameter, lighting conditions, opacity, gloss, light scattering, and overall perception by the naked eye. Previous investigations have indicated that translucency is the main factor that can significantly contribute to the esthetic characteristics of the different dental restoration materials. In the present literature review, we have discussed the translucency of human teeth and its relation to esthetic restorative materials. Comparing the translucency of the different restoration materials with the naturally occurring human enamel is essential for adequate validation of their clinical application. It has been demonstrated that for 1 mm thick human enamel, a mean value for the translucency parameter of 15-19 should be considered. We have also highlighted the differences between the different types of resin composites and different shade groups, and findings indicate the superiority of some types and shade groups over others, as previously discussed. However, it should be noted that further research is still needed to unify the variously estimated values for the translucency parameter among the different restoration materials. This can help clinicians adequately interpret these data and obtain satisfactory clinical and patient-related outcomes.